Micro-optical gyroscope using a PANDA ring resonator - Sa-Ngiamsak, Wisitsak; Sirawattananon, Chaiwat; Srinuanjan, Keerayoot; Mitatha, Somsak; Yupapin, Preecha P. (My University, 2012)
We propose a new system of a micro-optical gyroscope (MOG) using a micro-embedded system. This system is comprised of a modified add/drop filter known as a PANDA ring resonator, which can be applied to navigate the direction with 3-D axes. The optical total path length of a MOG has been expanded by mean of an enhanced ring or PANDA ears. Simulation results obtained have shown that the precision signal at the phase difference of rotation orbit (straight line, ellipse, circle, etc.,) as a function of the inertial rotation rate Ω based on the Sagnac effect is achieved. The dependence of the transmission characteristics of the PANDA ring on the coupling coefficients of directional couplers is studied. The mathematical model of the system is analyzed and simulated. © 2012 IEEE.
Keywords: Micro-optical gyroscope (MOG); PANDA ring resonator; Sagnac effect; three-axis gyroscopes